Influence of the Type of Sagittal Profile on Clinical Results of Lumbar Total Disk Replacement After a Mean Follow-Up of 39 Months. Issue 7 (August 2016) - Strube, Patrick; Hoff, Eike K.; Perka, Carsten F.; Gross, Christian; Putzier, Michael
Abstract : Study Design: Retrospective analysis of clinical and radiologic data of a prospective cohort study. Objective: To research the clinical differences after lumbar total disk replacement (TDR) with respect to the preoperative global and the adaptation at the local sagittal profile (SP) of the spine. Summary of Background Data: It was suggested that facet loads and degeneration are dependent on epidemiologically defined types of SP. Moreover, the success of TDR was related to segmental facet joint loads. The influences of the preoperative SP or of the changes of the local SP after TDR on the clinical outcome after TDR remain unclear. Methods: Fifty-two patients included in a prospective cohort study regarding lumbar single-level TDR L4/5 (n=22) or L5/S1 (n=30) because of degenerative disk disease (Modic ⩽2 degrees) were clinically (visual analog scale for back, leg, and overall pain; Oswestry Disability Index) and radiologically (extension-flexion radiographs, plain-spine, and whole-spine lateral radiographs in upright standing position) reevaluated after a minimum follow-up of 24 (24–69) months. On the basis of preoperative plain radiographs in upright standing position, patients were retrospectively assigned to 4 groups according to the individual sagittal profile type (SPT). In patients with persistent back pain, a facet infiltration at the index level was performed. Results: For all patients, an SPT could be defined. Global SP did not change compared with the preoperative state. All groups improved clinically over follow-up. At the last follow-up, types 1 and 4 demonstrated significantly inferior scores for pain and function. TDR-induced changes at the superior adjacent segment and the posterior disk height at the index level were also correlated to inferior clinical results. Infiltration test was positive in type 1–4: 67%, 40%, 33%, and 75%, respectively, of the symptomatic patients. Conclusions: We suggest SPTs 1 and 4 to represent a contraindication for lumbar TDR of levels L4/5 or L5/S1. Local adaptation in the adjacent segment to TDR may influence the clinical outcome as well.